Malaria in 2018 : looking to the past and moving into the future - Chia, Po Ying (2019)
World Malaria Day is observed and commemorated annually on 25 April in recognition of the ongoing global burden and the efforts to control it. Malaria is caused by Plasmodium parasites, of which 5 species are known to cause disease in humans, namely P. falciparum, P. vivax, P. ovale, P. malariae and P. knowlesi. It is a vector borne disease and is transmitted by Anopheles mosquitoes. Although potentially life threatening, prognosis is excellent if the disease is diagnosed early, and treated promptly with effective antimalarials.